Advancing physical activity measurement and guidelines in Canada (Applied Physiology, Nutrition, and Metabolism, 2007)
Advancing physical activity measurement and guidelines in Canada: a scientific review and evidence-based foundation for the future of Canadian physical activity guidelines. Contents: Research that informs Canada`s physical activity guides: an introduction Mark S. Tremblay, Roy J. Shephard and Lawrence R. Brawley Pages S1-S8 Canada`s physical activity guides: background, process, and development Michael T. Sharratt and William E. Hearst Pages S9-S15 Evidence-informed physical activity guidelines for Canadian adults Darren E.R. Warburton, Peter T. Katzmarzyk, Ryan E. Rhodes and Roy J. Shephard Pages S16-S68 Ageing and physical activity: evidence to develop exercise recommendations for older adults Donald H. Paterson, Gareth R. Jones and Charles L. Rice Pages S69-S108 Physical activity guidelines for children and youth Ian Janssen Pages S109-121 Physical activity for preschool children — how much and how? Brian W. Timmons, Patti-Jean Naylor and Karin A. Pfeiffer Pages S122-S134 Considerations for the development of a physical activity guide for Canadians with physical disabilities Kathleen A. Martin Ginis and Audrey L. Hicks Pages S135-S147 Physical activity of Aboriginal people in Canada T. Kue Young and Peter T. Katzmarzyk Pages S148-S160 Canada`s physical activity guides: has their release had an impact? Christine Cameron, Cora L. Craig, Fiona C. Bull and Adrian Bauman Pages S161-169 Physical activity guides for Canadians: messaging strategies, realistic expectations for change, and evaluation Lawrence R. Brawley and Amy E. Latimer Pages S170-S184 Limitations of Canada`s physical activity data: implications for monitoring trends Peter T. Katzmarzyk and Mark S. Tremblay Pages S185-S194 Abstract | Full text (PDF 184 kb, HTML) | Orders and Permissions Physical activity and inactivity profiling: the next generation Dale W. Esliger and Mark S. Tremblay Pages S195-S207 Incidental movement, lifestyle-embedded activity and sleep: new frontiers in physical activity assessment Mark S. Tremblay, Dale W. Esliger, Angelo Tremblay and Rachel Colley Pages S208-S217 Physical activity guidelines and guides for Canadians: facts and future Mark S. Tremblay, Roy J. Shephard, Lawrence R. Brawley, Christine Cameron, Cora Lynn Craig, Mary Duggan, Dale W. Esliger, William Hearst, Audrey Hicks, Ian Janssen, Peter T. Katzmarzyk, Amy E. Latimer, Kathleen A. Martin Ginis, Ashlee McGuire, Donald H. Paterson, Michael Sharratt, John C. Spence, Brian Timmons, Darren Warburton, T. Kue Young and Lori Zehr Pages S218-S224